Recent advancements of organic scintillators in enhancing the performance of fast neutron detection: A review - D. Arun Kumar; E. Parthiban (Nuclear Analysis, 2025)
Recent advancements in organic scintillators with neutron-gamma discrimination properties have significantly enhanced the performance of fast neutron detection, addressing critical needs in high energy physics, radiation therapy, homeland securities and well-logging industry. In this review, we summarize the latest developments in single-crystal organic materials focusing on their high light yield, excellent neutron-gamma discrimination and fast decay times. The first part of the review involves principles of scintillation, physical phenomenon and its mechanism of organic scintillation crystals. The second part presents the organic scintillation materials for fast neutron detection and its properties. Finally, in the third part delves into the potential applications and future prospects of organic scintillators, emphasizing their versatility in various detection systems. The findings underscore the pivotal role of organic scintillators in advancing fast neutron detection technology, paving the way for more efficient and reliable radiation monitoring solutions.